Imunobiologia da proteína 2 de superfície de amastigotas (ASP-2) de Trypanosoma cruzi - Claser, Carla [UNIFESP] (2008)
Pre-clinical vaccination studies provided evidence that the Amastigote Surface Protein-2 (ASP-2) is an important target for protective immunity against Trypanosoma cruzi infection. Based on the remarkable protective properties of ASP-2, we thought it would be important to evaluate its polymorphism in different strains of T. cruzi. Using polyclonal and monoclonal antibodies against a bacterial recombinant protein representing ASP-2 expressed by the Y strain, we confirmed the presence of ASP-2 associated epitopes on amastigotes of a T. cruzi II strain (Y), T. cruzi I strains (Sylvio X10/4, Dm28c, Tulahuén, G and Colombian) and a hybrid strain (CL-Brener). The ASP-2 primary structure in each different strain was determined from intracellular amastigotes cDNAs. Comparison of the primary structure of ASP-2 expressed by Y, CL-Brener, Tulahuén, G (G2) and Colombian strains confirmed the immunological data revealing a high degree of identity between them (>82%). In contrast, ASP-2 deduced sequences from Sylvio X10/4 and G (G1) strains displayed a limited identity to the others (<50%) and a high degree of identity between them (78.7%). Vaccination studies confirmed the structural data. Highly susceptible A/Sn mice immunized with cDNAs from Y (pIgSPclone9) or CL-Brener (pIgSPclone50) strains had a similar degree of protective immunity against a challenge with the Y strain. In contrast, the cDNA of the G strain (pIgSPclone62, G1) was significantly less effective. Overall, our study provides evidence that ASP-2 expressed by different T. cruzi strains share a high degree of structural and immunological identity. However, there are few strains with distinct forms of this protein in nature. To study the possible function of ASP-2, we firstly evaluated the binding of the recombinant protein to mammalian cells in culture. Although the recombinant protein binds to cultured cells, transfected parasites expressing ASP-2 on the surface do not induce intracellular Ca2+ mobilization in HeLa cells, an important phenomenon in host cells invasion. ASP-2 contains a C-terminal domain denominated FLY domain (VTVXNVFLYNR) that was shown to interact with cytokeratin (CK18), a protein abundant on the host cell cytoplasm. Based on these observations, we hypothesized xx that the interaction of the FLY domain of ASP-2 with CK18 could be a critical step for T. cruzi multiplication in the host cell cytoplasm. RNAi was used to knock down the expression of CK18 in HeLa cells in vitro. Following RNAi transfection, reduced level of CK18 mRNA and protein were confirmed by real time RT-PCR, Western blot and immunofluorescence. Following infection with trypomastigotes of Y, CL-Brener or Sylvio X10/4 strains of T. cruzi, we could not observe a significant reduction in the percentage of cells infected, indicating that parasite invasion was not significantly altered by the absence of CK18. However, CK18 RNAi transfected cells infected with trypomastigotes of Y or CL-Brener strains displayed a significant reduction in the number of intracellular parasites 48 hours later when compared with control cells. The reduced level of CK18 did not affect the number of intracellular parasites of a third parasite strain (Sylvio X10/4). Colocalization experiments showed that parasites of Y strain, but not Sylvio X10/4 strain, may interact with CK18. The reduced level of CK18 did not affect the His-65kD recombinant protein binding to HeLa cells, nor the ERK1/2 phosphorilation. Our studies demonstrated that RNAi can be useful to reduce the CK18 expression in HeLa cells in vitro and the inhibition of CK18 does not interfere with T. cruzi invasion, but it seems to reduce the multiplication of intracellular forms in strains that interact with the CK18. Our results also showed that the CK18 is not necessary for the recombinant protein binding to HeLa cells nor the activation of ERK1/2 pathway signaling induced by ASP-2.